Outstanding universal values of the Malaysian forests - Md. Khalid, Rasyikah; Kamaruddin, Hanim; Yaakob, Adzidah; Wook, Izawati; Sulaiman, Siti Sarah; Mustafa, Maizatun (AESS Publications, 2018)
Two national parks in Malaysia have been recognized by the Convention Concerning the Protection of the World‟s Cultural and Natural Heritage as the world heritage sites; the Gunung Mulu National Park and Kinabalu Park. None of the forest in Peninsular Malaysia has achieved that status but four have made it through the nomination list. The Malaysian government‟s recent initiative was to list three reserved areas, namely the Forest Research Institute Malaysia (FRIM), the Royal Belum National Park and the Gombak Selangor Quartz Ridge. The nomination for the UNESCO World Heritage Site is indeed a good move in protecting the Malaysian forest. Even though there is no direct mention of „forest‟ stated under the Convention, it tacitly indicates the importance of the conservation of natural forest habitat for flora and fauna and a heritage for humankind. An outstanding forest site shall be conferred a world heritage status when it possesses at least one of the criteria of an Outstanding Universal Value or OUV. Ten criteria are listed as OUV in the Operational Guidelines for the Implementation of the World Heritage Convention and it is divided as a cultural or natural heritage. This paper explores on the OUV of Malaysian forests, either included in or nominated to the World Heritage List. It describes the different OUV opted by different forest and that exemplifies the diversity and uniqueness of Malaysian forest.